Implementation Trendelenburg Position In Septic Shock Patients In The Intensive Care Unit : A Case Report - Rausanfikra, Syiffa Salsabila; Mirwanti, Ristina; Nuraeni, Aan (Alta Dharma Publisher, 2024)
Introduction: Shock is a clinical syndrome that occurs due to hemodynamic and metabolic disorders characterized by failure of the circulatory system to maintain adequate perfusion to the body's vital organs. Objective: This study aimed to describe the implementation of the Trendelenburg position intervention in patients with septic shock in the intensive care unit. Method: Researchers used the case report method to explain the implementation of the Trendelenburg position intervention in shock management. Result: In this study, the Trendenburg position can increase perfusion in patients with septic shock at the beginning of the maneuver but it does not last long. This position helps increase the perfusion of vital organs by improving blood flow to the brain and other organs in the patient. Recommendation: This study concludes that the Trendelenburg position has a positive effect on patients with septic shock if combined with other interventions and pharmacological support. Keywords: Intensive Care Unit, Shock, Trendelenburg